Better skills acquired to meet industries' needs - UMP, PNC
A total of 120 Universiti Malaysia Pahang (UMP) undergraduates completed the 'Degree++' programme conducted by the Faculty of Chemical & Natural Resources Engineering (FKKSA). They were the first batch to undergo the programme that involved industries especially those from the oil and gas sector.